(untitled) (Research, Society and Development, 2025)
The purpose of this study is to evaluate the morphological and electrical properties of a composite made from vulcanized natural rubber (VNR) reinforced with PZT particles and leather residue (LR). The materials were processed using a simple open-roll mixing method, keeping constant proportions of natural rubber and leather residue, while varying the PZT content at 25 and 50 phr. Scanning electron microscopy revealed homogeneous dispersion of both the LR and PZT particles within the VNR matrix, with no visible agglomerations, confirming the effectiveness of the mixing process. Electrical impedance analyses indicated that all composites exhibited frequency-dependent conductivity, a characteristic of disordered solid materials. Samples containing higher PZT concentrations showed increased conductivity at low frequencies, mainly due to dipole movement within the ceramic phase. Dielectric permittivity and capacitance also decreased with increasing frequency, while the composite with 50 phr of PZT presented the highest dielectric constant and energy storage capacity. Mechanical tests demonstrated that the inclusion of LR enhanced tensile strength and reduced elongation at break, acting as a fibrous reinforcement. The addition of PZT particles increased stiffness, resulting in slightly more brittle behavior. The VNR-LR/PZT three-phase composite with 50 phr PZT achieved the best balance between the mechanical strength and electrical performance. Overall, the results confirm that the developed composite exhibits promising multifunctional behavior suitable for piezoelectric sensing and energy-harvesting applications. Furthermore, the reuse of leather waste provides an environmentally responsible alternative, converting an industrial residue into a functional, high-value material with both technological and ecological benefits.